From Eden to Agora: The E-Learning Trading Zone - Sturm, Sean; Carter, Susan (Critical Studies in Teaching and Learning, 2023)
E-learning is not just a learning and teaching innovation; it also signals a shift in human cognition and communication. The lexicon of e-learning borrows from the barren lexicon of information science: of users, usage and usability (Gould and Lewis, 1985), or of information-seeking and affordances (Pirolli and Card, 1999). Deep e-learning requires a more fecund idiom, a new myth: of the digital agora, an e-learning ‘trading zone’ (Mills and Huber, 1995). Here we reflect on the process of shaping an electronic version of our generic doctoral skills sessions, during which it occurred to us that, to match the benefits of interactivity in face-to-face teaching and learning and to be transformative of academic subjectivity, e-learning must be truly performative, rather than merely informative; e-learners (and e-teachers too) must enact the skills they hope to learn (or teach).